Analysis of the Budget Plan for the Construction of Freja House BSD Mass Buildings using the BOW, SNI 2008 & 2021 AHSP Methods - Renaldo Pudja Pangestu; Edison H Manurung; Kerlima Hutagaol (PT FORMOSA CENDEKIA GLOBAL, 2023)
To plan a project budget, the estimator must have clear and economical method guidelines. The benefits obtained by an Estimator depend on his skills in making cost estimates. If the price bid submitted in the auction process is too high, it is likely that the Estimator will suffer a loss. On the other hand, if you win an auction at a price that is too low, you will experience difficulties in the future. Therefore, cost estimates play an important role in project implementation to plan and control resources such as materials, labor, services and time. In Indonesia, there are methods for planning the unit price of project budget costs, namely BOW (Burgelijke Openbare Werken), SNI 2008 and AHSP 2021. Contractors generally make bid prices based on analysis that is not entirely guided by BOW (Burgelijke Openbare Werken) analysis, SNI 2008 and AHSP 2021 Contractors are more inclined to calculate the unit price of work based on their own analysis based on previous experience in completing a construction job. This study aims to find out what method is the most economical and to be a reference for estimators planning construction costs using the method that applies in Indonesia, not using the method that is self-analyzed.